Reduced Hippocampal Neurogenesis in Mice Deficient in Apoptosis Repressor with Caspase Recruitment Domain (ARC). (15th September 2019) - Kronenberg, Golo; Gertz, Karen; Uhlemann, Ria; Kuffner, Melanie T.C.; Kirste, Imke; An, Junfeng; Jadavji, Nafisa M.; Schott, Bjoern H.; Scheffel, Thomas; Endres, Matthias; Hellweg, Rainer; Harms, Christoph
Abstract: In the adult hippocampal dentate gyrus (DG), the majority of newly generated cells are eliminated by apoptotic mechanisms. The apoptosis repressor with caspase recruitment domain (ARC), encoded by the Nol3 gene, is a potent and multifunctional death repressor that inhibits both death receptor and mitochondrial apoptotic signaling. The aim of the present study was to parse the role of ARC in the development of new granule cell neurons. Nol3 gene expression as revealed by in situ hybridization is present in the entire dentate granule cell layer. Moreover, a comparison of Nol3 expression between FACS-sorted Sox2-positive neural stem cells and Doublecortin (DCX)-positive immature neurons demonstrates upregulation of Nol3 during neurogenesis. Using ARC-deficient mice, we show that proliferation and survival of BrdU birth-dated cells are strongly reduced in the absence of ARC while neuronal-glial fate choice is not affected. Both the number of DCX-positive cells and the number of calretinin (CR)-positive immature postmitotic neurons are reduced in the hippocampus of ARC −/− mice. ARC knockout is not associated with increased numbers of microglia or with microglia activation. However, hippocampal brain-derived neurotrophic factor (BDNF) protein content is significantly increased in ARC −/− mice, possibly representing a compensatory response. Collectively, our results suggest that ARC plays a critical cell-autonomous role in preventing cell death during adult granule cell neogenesis. Highlights: Reduced net hippocampal neurogenesis in ARC −/− mice ARC knockout not associated with increased microglia density or activation Increased BDNF concentrations in microdissected left hippocampus of ARC −/− mice